Genomic insights into Verticillium: a review of progress in the genomics era - Sayari, M.; Dolatabadian, A.; El-Shetehy, M.; Daayf, F. (Frontiers in Microbiology, 2024)
Genomics has emerged as a great tool in enhancing our understanding of the biology of Verticillium species and their interactions with the host plants. Through different genomic approaches, researchers have gained insights into genes, pathways and virulence factors that play crucial roles in both Verticillium pathogenesis and the defence responses of their host organisms. This review emphasizes the significance of genomics in uncovering the mechanisms that underlie pathogenicity, virulence, and host resistance in Verticillium fungi. Our goal is to summarize recent discoveries in Verticillium research highlighting progress made in comprehending the biology and interactions of Verticillium fungi. The integration of genomics into Verticillium studies has the potential to open avenues for developing strategies to control diseases and produce crop varieties resistant to verticillium, thereby offering sustainable solutions for enhancing agricultural productivity.